Male Wage Inequality and Characteristics of "Early Mover" Marriages - Hani Mansour; Terra McKinnish (Institute of Labor Economics (IZA), 2022)
Previous work shows that higher male wage inequality decreases the share of ever married women in their 20s, consistent with the theoretical prediction that greater male wage dispersion increases the return to marital search. Consequently, male wage inequality should be associated with higher husband quality among those "early-mover" women who choose to forgo these higher returns to search. We confirm using U.S. decennial Census and American Community Survey (ACS) data from 1980-2018 that married women ages 22-30 in marriage markets with greater male wage inequality are more likely to marry up in education and in husband's occupation. We additionally consider whether male wage inequality increases wage uncertainty, leading women to prefer older husbands who can send stronger signals of lifetime earnings. We confirm that higher male wage inequality is also associated with a larger marital age gap.
Keywords: J12; J24; 330; marriage; marital search; marital sorting; inequality; male wages